Nylon Filter Arrays Reveal Differential Gene Expression in Proteoid Roots of White Lupin in Response to Phosphorus Deficiency - Uhde-Stone, Claudia (American Society of Plant Biologists, 2003)
White lupin (Lupinus albus) adapts to phosphorus deficiency (−P) by the development of short, densely clustered lateral roots called proteoid (or cluster) roots. In an effort to better understand the molecular events mediating these adaptive responses, we have isolated and sequenced 2,102 expressed sequence tags (ESTs) from cDNA libraries prepared with RNA isolated at different stages of proteoid root development. Determination of overlapping regions revealed 322 contigs (redundant copy transcripts) and 1,126 singletons (single-copy transcripts) that compile to a total of 1,448 unique genes (unigenes). Nylon filter arrays with these 2,102 ESTs from proteoid roots were performed to evaluate global aspects of gene expression in response to −P stress. ESTs differentially expressed in P-deficient proteoid roots compared with +P and −P normal roots include genes involved in carbon metabolism, secondary metabolism, P scavenging and remobilization, plant hormone metabolism, and signal transduction.